2007
DOI: 10.1111/j.1365-2044.2007.05096.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending low‐dose epidural analgesia in labour for emergency Caesarean section – a comparison of levobupivacaine with or without fentanyl*

Abstract: SummaryWomen in labour receiving epidural analgesia with 15 ml bupivacaine 0.1% and 2 lg.ml )1 fentanyl followed by 10-15-ml top-ups as required, who needed Caesarean section, were randomly allocated to receive 20 ml levobupivacaine 0.5% over 3 min with either 75 lg fentanyl (1.5 ml) or 1.5 ml saline. Further top-ups or inhaled or intravenous supplementation were given for breakthrough pain. Time to onset (loss of cold sensation to T4 and touch sensation to T5 bilaterally), quality of analgesia and side-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…12 However, in recent studies, inadequate surgical anesthesia after conversion of ELA to ESA for CD necessitated conversion to GA in 2.5-20% of cases and provision of additional analgesia was even more frequent. [13][14][15][16][17][18][19] Only one underpowered study reported a conversion rate to GA of 0%. 20 In fact, inadequate ESA has led to litigation against anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, in recent studies, inadequate surgical anesthesia after conversion of ELA to ESA for CD necessitated conversion to GA in 2.5-20% of cases and provision of additional analgesia was even more frequent. [13][14][15][16][17][18][19] Only one underpowered study reported a conversion rate to GA of 0%. 20 In fact, inadequate ESA has led to litigation against anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Only after it has been demonstrated that the insertion or ventilation characteristics are clinically different, and after correcting the results for the increased experience with this instrument, can one conclude that our study is dated and confusing. Local anaesthetic-opioid mixture for emergency Caesarean section I read with interest the study by Malhotra and Yentis [1] which shows, using a randomised design, that adding fentanyl to the top-up solution of levobupivacaine does not improve intra-operative analgesia during emergency Caesarean section in patients who were receiving a bupivacaine-fentanyl mixture during labour. I can easily agree with the authors that there are no previous studies which have investigated the use of fentanyl in similar patients receiving levobupivacaine.…”
Section: A Replymentioning
confidence: 99%
“…I was interested to see the paper by Dr Klaver and colleagues comparing novice anaesthetists' performance with the LMA ProSeal Ò (PLMA, Intavent Orthofix, Maidenhead, UK) and Laryngeal Tube-S (LTS, VBM GmbH, Sulz, Germany) [1]. Unfortunately, much of the data in the paper are redundant as the LTS was withdrawn by the manufacturers in 2005 when it was superseded by the LTS mark II (LTS II, VBM GmbH).…”
mentioning
confidence: 99%
“…A similar need for additional preoperative top ups or spinal anaesthesia to rescue women receiving levobupivacaine has been reported by others. 10,11 Although the elapsed time between the last labour top up and the bolus dose for emergency delivery was longer in the levobupivacaine group and could be seen by some as a confounding factor, it is important to note that there were no differences between the two groups in any of the pre-existing block levels before the top up for caesarean section. This similarity of block levels may have been because the duration of the labour epidurals in the levobupivacaine group was also significantly longer than in the LEF group.…”
Section: Discussionmentioning
confidence: 96%
“…Other similar studies using different local anaesthetics have also found no relationship between these factors and the speed of block onset. 1,10,12,13 A limitation of our study was that it was not double blind and the anaesthetists may have been more familiar with the behaviour of the LEF mixture than with levobupivacaine for caesarean section. We do not believe that the unblinded nature of the study would have had a significant impact on the results.…”
Section: Discussionmentioning
confidence: 97%